Creation of Web Service System and Educational Application Fire Fighting Service - Putra, Firmansyah; Perdana, Dhika Aulia; Hasanah, Deby Safitri; Siregar, Ibnu Riski Ganda; Putra, Eka; Tambunan, Toman Sony (Cattleya Darmaya Fortuna, 2024)
Fire is one of the disasters that can cause significant losses both in terms of material and casualties. Therefore, an effective service and education system fixed to increase public awareness and responsiveness to fire incidents. This study aims to develop an integrated web service system and educational application for fire department services. This system is designed using modern web technologies such as HTML, CSS, and JavaScript, and frameworks like React.js for user interface development. The backend uses Node.js and Express.js, while the database used is MySQL